Aplikasi Pembelajaran Bangun Ruang dengan Augmented Reality (Studi Kasus : Sdn Rorotan 07 Jakarta) - Selvana Arma Putra; Diah Aryani; Noviandi Noviandi; Hani Dewi Ariessanti (FORMAT, 2023)
The use of technology and reliance on the internet has altered students' learning practices, especially how they approach mathematics. As a result, a novel method of teaching mathematics is required, particularly for geometric concepts that are challenging for children to grasp. For students to better comprehend geometric forms and volume formulas, this study intends to develop spatial learning applications incorporating augmented reality (AR). The method employed in this study is called the Multimedia Development Live Cycle (MDLC), and it includes the steps of ideation, design, material collecting, assembly, testing, and distribution. The results showed that this application succeeded in increasing students' understanding in the form of geometric shapes through the use of spatial learning applications with augmented reality. This was effective in increasing students' understanding of using 3D objects and interactions through applications made students more interested and motivated to learn mathematics.